Correlation between Lifestyle Factors and COVID-19 Indices: An Ecological Study - Fatemeh Rezaei; Mousa Ghelichi-Ghojogh; Farzaneh Mobasheri; Sanaz Amiri; Elahe Piraee; Seyed Sina Dehghani; Amir Hossein Hassani; Kimia Jokari; Alireza Mirahmadizadeh (Journal of Health Sciences and Surveillance System)
Background: Coronavirus disease of 2019 (COVID-19) became a public health threat to global public health in late 2019. This study aimed to investigate the correlation between lifestyle factors and the COVID-19 epidemiological indicators, including cumulative incidence rate, the cumulative rate of death, recovery rate, and case fatality rate.Methods: In this ecological study, aggregate data were used. Information about COVID-19 for each country was retrieved from https://www.worldometers.info/ from the date of the first report until November 30th, 2020. The information on the prevalence of smoking, alcohol consumption, and obesity in 2019 was collected from https://www.indexmundi.com/. Moreover, the information on the prevalence of physical inactivity was obtained from the WHO website. We drew scatter plots of lifestyle factors based on COVID-19 indices.Results: Results showed that the cumulative incidence rate and cumulative rate of death had significant direct correlations with the prevalence of obesity, physical inactivity, smoking, and alcohol consumption (P<0.05). This means that the countries with a high prevalence of obesity, physical inactivity, smoking, and alcohol consumption had increased indicators such as the cumulative incidence rate and cumulative rate of death (P<0.05). There were also significant inverse correlations between the recovery rate and the prevalence of smoking and alcohol consumption (P<0.05).Conclusion: There are significant correlations between the cumulative incidence rate, the cumulative rate of death, and the recovery rate of COVID-19 with unhealthy lifestyle behaviors. Therefore, it is necessary to develop lifestyle modification strategies that can lead to reduction of the morbidity and mortality of this disease.